(untitled) (Innovate Conferences, 2025)
In a globalized world, the intersection of literary translation and copywriting offers unique opportunities for effective communication. This article explores how the skills developed through literary translation—such as cultural sensitivity, narrative construction, and emotional resonance—enhance copywriting strategies. By examining notable advertising campaigns, the discussion highlights the importance of cultural nuances, compelling storytelling, attention to language, adaptability in tone, and emotional engagement. Ultimately, blending literary techniques with advertising practices enriches brand communication, fostering deeper connections with diverse audiences.